2014
DOI: 10.1179/0886963413z.0000000001
|View full text |Cite
|
Sign up to set email alerts
|

Clinician accuracy when subjectively interpreting articulating paper markings

Abstract: Subjective Interpretation is an ineffective clinical method for determining the relative occlusal force content of tooth contacts. The reported low scores obtained from a large group of participant dentists suggest clinicians are unable to reliably differentiate high and low occlusal force from looking at articulating paper marks. This longstanding method of visually observing articulating paper marks for occlusal contact force content should be replaced with a measurement-based, objective method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 11 publications
1
47
0
2
Order By: Relevance
“…The authors suggested that long‐standing controversies about occlusal mark interpretations are focused on artefactual observations, and are not scientific in nature. This has been confirmed in other studies where clinician occlusal force perceptions drawn from how the ink markings appear visually correlates very poorly with the actual occlusal force present in different sized markings …”
supporting
confidence: 76%
See 1 more Smart Citation
“…The authors suggested that long‐standing controversies about occlusal mark interpretations are focused on artefactual observations, and are not scientific in nature. This has been confirmed in other studies where clinician occlusal force perceptions drawn from how the ink markings appear visually correlates very poorly with the actual occlusal force present in different sized markings …”
supporting
confidence: 76%
“…However, the study’s Conclusions presented in the Abstract are misleading to the reader with respect to the T‐Scan sensor, specifically; “…popular occlusal detection products alter the occlusal contact forces, and therefore, their markings cannot characterize the actual occlusion. ” This statement only applies to the tested marking materials, because although the T‐Scan sensor does alter the load moments of the casts (like all the interocclusal indicators tested by the authors), the T‐Scan does not “characterize occlusion” by marking the teeth with ink smears, which are then poorly subjectively observed by clinicians . So to suggest that because the T‐Scan sensor sits between the teeth (while not marking them with ink), it is unable to “characterize occlusion,” is a completely false representation of the T‐Scan sensor’s true occlusal force and timing measurement capabilities.…”
mentioning
confidence: 99%
“…In the present study, although the occlusal contact areas were increased on the sides treated with ISFPPs, the number of restorative units was a more important factor in explaining the improvement in unilateral masticatory performance and satisfaction with chewing ability. This may be because clinicians are unable to differentiate high‐ and low‐force contacts reliably on articulating paper (Kerstein & Radke, ), even though articulating paper and occlusal foils are the most widely applied methods for occlusal adjustment and have been used to assess the number of occlusal contacts in research (Caro, Peraire, Martinez‐Gomis, Anglada, & Samsó, ). We cannot dismiss the possibility that using an interocclusal distance other than 200 µm might have made the increase in occlusal contact area more relevant.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because clinicians are unable to differentiate high-and low-force contacts reliably on articulating paper (Kerstein & Radke, 2014), even though articulating paper and occlusal foils are the most widely applied methods for occlusal adjustment and have been used to assess the number of occlusal contacts in research (Caro, Peraire, Martinez-Gomis, Anglada, & Samsó, 2005). We cannot dismiss the possibility that using an interocclusal distance other than 200 µm might have made the increase in occlusal contact area more relevant.…”
Section: Ta B L Ementioning
confidence: 97%
“…Kerstein and Radke [6] asked 295 dentists to look at the same paper markings, and found clinician interpretation of the paper marks varied widely. Their study revealed the 295 dentists chose correct contacts only 12.8% of the time when using the principles of mark size and color-depth as indicators of occlusal force levels.…”
Section: The Dogma Of Occlusal Paradigms: What Do We Really Have Figumentioning
confidence: 99%